REKONSTRUKSI TERHADAP KONSEP SUNNAH DALAM PEMIKIRAN MUHAMMAD SYAHRUR - Mia Fitriah El karimah (al Dhikra | Jurnal Studi Qur'an dan Hadis, 2023)
The Sunnah of the Prophet SAW. is one of the sources of law in Islam; more precisely, it is in the second position as a source of direction. One of the aggressive figures in reconstructing the sunnah concept is Muhammad Syahrur. Syahrur is a Muslim thinker who grew up in detailed scientific studies and had never studied Islamic science intensively. It offers a contemporary reading of the sources of Islamic law, including the Sunnah. In his view, understanding religious texts is unnecessary; it is always required to prioritize the interpretation of traditional ulama. Because it should be interpreted according to its time. He then boldly rejected the revelation of the Sunnah and its capacity as a source of law. This research model is a complete literature study with primary data is his work; Al-Sunnah al-Rasuliyyah wa al-Sunnah al-Nabawwiyah Ru'yah Jadidah. Through a descriptive analysis approach, this research reveals the concept of the Sunnah of Syahrur. Syahrur defines the Sunnah as a method (way, manhaj) to apply the legal provisions of the Umm al-Kitab without outside the limits set by Allah in hudud matters. The results of this study indicate that before discussing the Sunnah in-depth, Syahrur first describes some of the terminologies in the Qur'an that are associated with the Sunnah in the Qur'an. Explain obedience. This discussion aims to provide a correct understanding of the concept of Sunnah. Because the concept of Sunnah that must be adhered to will be clearly understood if the terminology has been understood. Three terminologies in the Qur'an go with the "sunnah" in explaining obedience: al-iṭṭibā', al-qudwah, and al-uswah. Departing from the distinction between the three terms above, Syahrur formulated a new understanding of the Sunnah: tends to be synonymous with ijtihad itself, not a source of law in ijtihad.